Comprehensive molecular and cellular studies suggest avian scutate scales are secondarily derived from feathers, and more distant from reptilian scales. Issue 1 (December 2018) - Wu, Ping; Lai, Yung-Chih; Widelitz, Randall; Chuong, Cheng-Ming
Abstract Amniote skin appendages such as feathers, hairs and scales, provide thermoregulation, physical protection and display different color patterns to attract a mate or frighten an adversary. A long-standing question is whether "reptile scale" and "avian leg scales" are of the same origin. Understanding the relation between avian feathers, avian scales and reptilian scales will enhance our understanding of skin appendage evolution. We compared the molecular and cellular profiles in chicken feather, chicken scales and alligator scales and found that chicken scutate scales are similar to chicken feathers in morphogenesis at the early placode stage. When we compared the expression of the recently identified feather-specific genes and scale-specific genes in these skin appendages, we found that at the molecular level alligator scales are significantly different from both chicken feathers and chicken scales. Furthermore, we identified a similarly diffuse putative stem cell niche in morphologically similar chicken and alligator scales. These putative stem cells participate in alligator scale regeneration. In contrast, avian feathers have a more condensed stem cell niche, which may be responsible for cycling. Thus, our results suggest that chicken and alligator scales formed independently through convergent evolution.